'Why Should Holidays Come in the Way of School?' Situating Girls' Experiences of Schooling. (June 2015) - Roy, Sangeeta
This article explores girls' experiences of schooling in a cluster of villages in the Mahabubnagar district in Telangana, India, arguing that the processual conception of schooling is one that commences before the access of girls to school. It includes the social learning of distributive justice through family, community and religion that influences girls' perceptions of differential entitlements to educational resources due to their gender. These perceptions are simultaneously reinforced and contested by the school, contouring their engagement with educational resources. Drawing from the theoretical frame of feminist standpoint epistemology this study uses interviews and focus group discussions to engage with its participants. It focuses on the specificities of individual assertions and contestations of girls, as well as the complex responses of affirmation and injunctions of parents, teachers and other members of the community who impact their experiences. In doing so it marks a departure from the linear rhetoric of the dismal experiences of girls and boys in government schools in India.